Does persistence pay off? Accessing social activities with a foreign-sounding name. Issue 10 (7th June 2021) - Dietl, Helmut M.; Gomez-Gonzalez, Carlos; Moretti, Paolo; Nesseler, Cornel
ABSTRACT: In this paper, we examine if a slight behavioural modification has an influence on discrimination. Specifically, we use a field experiment based on emails to observe if persistence increases the chances of joining a social group. We find that native- or foreign-sounding names are equally successful when being persistent. However, non-persistent individuals with foreign-sounding names suffer from discrimination. The results show that persistent individuals can be especially interesting in the context of field experiments.